Acidic polyurethane rigid foam and preparation method thereof

By introducing organic acids into the polyurethane hard foam and adjusting the catalyst content and reaction conditions, the problem of the increase in the thermal conductivity of the polyurethane hard foam when using environmentally friendly foaming agents is solved, and lower thermal conductivity and higher strength are achieved and better production efficiency.

CN115572361BActive Publication Date: 2025-02-18WANHUA CHEM NINGBO RONGWEI POLYURETHANE
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202110683707.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-06-21
Publication Date
2025-02-18
Estimated Expiration
2041-06-21

AI Technical Summary

Technical Problem

When using environmentally friendly foaming agents, the thermal conductivity of polyurethane rigid foam increases, which cannot meet the national energy consumption standards. At the same time, the cost of raw materials is high, which affects industrial efficiency.

Method used

The polyurethane rigid foam formula containing organic acid is adopted to adjust the catalyst content and reaction conditions through organic acids, reduce the size of the cell and improve the surface maturation and strength of the foam.

Benefits of technology

It effectively reduces the thermal conductivity of the foam, improves the strength and surface maturation performance of the foam, reduces the cost of raw materials, and optimizes the production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003123484020000021
    Figure BDA0003123484020000021
  • Figure BDA0003123484020000032
    Figure BDA0003123484020000032
  • Figure BDA0003123484020000041
    Figure BDA0003123484020000041
Patent Text Reader

Abstract

The present invention provides a polyurethane rigid foam under acidic conditions and a preparation method thereof. An organic acid is added to the polyurethane rigid foam during the preparation process. The acidic conditions can reduce the reaction activity of the polyurethane catalyst, thereby increasing the content of the catalyst, and the carboxyl group in the organic acid can react with isocyanate to produce CO2, thereby reducing the water content in the formula and improving the adhesion of the foam surface. In the later stage of the reaction, the foam begins to gel and the acid disappears. The high catalyst content can make the foam surface solidify rapidly and reduce the bubbles on the surface, thereby showing a more excellent comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polyurethane materials, and in particular relates to an acidic polyurethane rigid foam and a preparation method thereof. Background Art

[0002] Due to its advantages of light weight, high strength and easy molding, polyurethane rigid foam is widely used in refrigerators, freezers, containers, etc. It has developed rapidly and has also undergone many technical updates.

[0003] Polyurethane rigid foam has a very low density. The density is about 10-300kg / m 3 , which is equivalent to a fraction or even a few tens of the density of ordinary foamed plastics. Polyurethane rigid foam has excellent thermal insulation performance, and its thermal conductivity is much lower than that of nylon, resin, polypropylene and other polymer plastics. Due to its excellent performance, it has flourished at home and abroad in recent years, and has achieved many technological breakthroughs to meet the needs of different fields.

[0004] While polyurethane is booming, it has also had some negative impacts on the environment. In order to protect the atmospheric ozone layer, the polyurethane industry has replaced the foaming agent CFC. The emergence of alternative foaming agents has found a new way out for the polyurethane industry. The standard for foaming agent alternative products is that the ozone depletion potential is equal to zero and the global warming potential is as low as possible. However, the gaseous thermal conductivity of CFC alternative foaming agents is high, and the gaseous thermal conductivity accounts for more than 50% of the thermal conductivity of polyurethane rigid foam. The increase in gaseous thermal conductivity leads to an increase in the thermal conductivity of the overall polyurethane foam, and the energy consumption of insulation equipment such as refrigerators, freezers, water heaters, etc. increases, which does not meet national standards. Therefore, how to use environmentally friendly foaming agents without losing the thermal conductivity of foam or the energy consumption of household products has become a difficult problem in the development of polyurethane.

[0005] Some factories choose to use polyester as the main raw material, but polyester itself has poor demoulding performance, poor foam surface maturation, and slow curing of the central foam fiber skeleton. Therefore, the curing time can only be extended on site, affecting production efficiency and increasing labor costs. Some factories also use the method of adding a small amount of fluorine-containing additives, but the price of fluorine-containing additives is several times or even dozens of times that of basic polyether materials. The use of fluorine-containing additives will increase the cost of formula raw materials very much. The profit of a single refrigerator itself is limited. After using additives, the cost pressure of the factory will increase significantly. Therefore, how to optimize the formula thermal conductivity while reducing cost increases has become a technical difficulty for polyurethane materials. Summary of the invention

[0006] The object of the present invention is to provide a polyurethane rigid foam, which has a low increase in raw material cost, meets the requirement of a foam thermal conductivity without increasing the thermal conductivity of the foam when using a foaming agent with a high global warming potential, reduces the cell size, increases the maturation of the foam surface, and improves the foam strength.

[0007] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:

[0008] A polyurethane rigid foam, wherein the raw materials of the polyurethane rigid foam contain an organic acid, and the raw materials of the polyurethane rigid foam comprise the following components:

[0009]

[0010]

[0011] In the present invention, the composite polyether comprises: 89.5-94 parts of mixed polyether polyol, 3.5-5.5 parts of composite catalyst, 1.5-3.5 parts of surfactant, and 1.0-2.5 parts of water.

[0012] In the present invention, the mixed polyether polyol in the combined polyether comprises one or more of the following polyols:

[0013] Polyether polyol A: prepared by addition reaction of sorbitol as initiator with propylene oxide, with a viscosity of 25,000-35,000 mPa.s, a hydroxyl value of 350-550 mgKOH / g, and a functionality of 5.5-6.0;

[0014] Polyether polyol B: sucrose and glycerol are used as initiators, and undergo addition reaction with propylene oxide, with a viscosity of 8,000-15,000 mPa.s, a hydroxyl value of 450-600 mgKOH / g, and a functionality of 4.6-5.8;

[0015] Polyether polyol C: o-toluenediamine is used as the initiator, and first reacts with ethylene oxide for addition reaction. After the reaction, propylene oxide is added for addition reaction. The viscosity is 35,000-55,000 mPa.s, the hydroxyl value is 340-460 mgKOH / g, and the functionality is 3.4-3.9;

[0016] Polyether polyol D: Diethylene glycol is used as an initiator, and undergoes an addition reaction with propylene oxide. The viscosity is 50-100 mPa.s, the hydroxyl value is 200-300 mgKOH / g, and the functionality is 2.0.

[0017] In the present invention, the content of the combined catalyst in the combined polyether is positively correlated with the content of the organic acid, and preferably the content of the catalyst and the content of the organic acid have the following relationship:

[0018]

[0019] Where m0 is the mass of the combined catalyst without organic acid, m e is the mass of the combined catalyst, m c The mass of organic acid.

[0020] In the present invention, the combined catalyst in the combined polyether is: one or more of opalescent pentamethyldiethylenetriamine, tetramethylhexanediamine and bis-dimethylaminoethyl ether; one or more of gel-type catalysts dimethylbenzylamine, dimethylcyclohexane, triethylenediamine and methylimidazole; one or more of trimerization catalysts potassium acetate, hexahydrotriazine and quaternary ammonium salt.

[0021] In the present invention, the surfactant in the combined polyether is a silicon surfactant, preferably an organic silicon surfactant, more preferably one or more of silicone oil L6861, silicone oil B8481, silicone oil RW-E, Y16368 and silicone oil B84813.

[0022] In the present invention, the polyisocyanate is polymeric MDI, preferably polymeric MDI with an NCO content of 30 wt% to 32 wt%, more preferably one or more of Wanhua PM-200, Wanhua PM-2010 and Wanhua PM-400; preferably, the mass content of the polyisocyanate has the following formula:

[0023]

[0024] Among them, m b is the mass of isocyanate, m a is the mass of the combined polyether, m d is the mass of foaming agent, m c is the mass of organic acid, M c is the molecular weight of organic acid.

[0025] In the present invention, the general structural formula of the organic acid is as follows:

[0026]

[0027] Wherein, n is an integer not less than 0, preferably an integer of 0-3, and R is -CH3 or -Ph; preferably, the -COOH group contained in the organic acid can react with isocyanate to produce CO2, which is retained in the pores, and the reaction formula is as follows:

[0028]

[0029] The above organic acid is acidic in the combined material, which can reduce the activity of the catalyst. Under the condition of ensuring the same drawing time, the content of the catalyst can be greatly increased. In the later stage of the reaction, the foam is quickly drawn from liquid to solid. In this process, the acid disappears, the activity of the catalyst is instantly increased, and the movement of the foam is reduced, so that there are better surface bubbles after the foam solidifies. Because the acid increases the catalyst content, when the acid disappears in the later stage, it is equivalent to the increase of the catalyst content in the ordinary system. Therefore, the foam maturation and demolding performance can be greatly improved. Although the activity of the catalyst is reduced, more active sites are formed in the early stage, resulting in finer pore size, lower thermal conductivity of the foam, and higher strength.

[0030] In the present invention, the foaming agent is a single foaming agent or a mixed foaming agent, which at least contains a CP foaming agent.

[0031] Another object of the present invention is to provide a method for preparing the polyurethane rigid foam.

[0032] A method for preparing a polyurethane rigid foam, wherein the rigid foam is the above-mentioned polyurethane rigid foam, and the preparation method comprises the following steps:

[0033] S1: uniformly mixing a mixed polyether polyol, a surfactant, a composite catalyst and water, and cooling the mixture to obtain a combined polyether mixture A;

[0034] S2: adding organic acid to mixture A, shaking, standing, and cooling to obtain mixture B;

[0035] S3: After the mixture B and the foaming agent are uniformly mixed, a mixture C is obtained;

[0036] S4: Add the mixture C and the polyisocyanate into independent foaming machine material tanks respectively, mix and foam them under high pressure, and then inject them into a mold to obtain polyurethane rigid foam.

[0037] In the present invention, the cooling to below 15°C is performed in steps S1 and S2; the conditions for high-pressure foaming in step S4 are material temperature of 15-20°C, preferably material temperature of 17-18°C, pressure of 100-150 barG, preferably pressure of 125-130 barG.

[0038] In the present invention, the mold in step S4 is a horizontal mold and / or a vertical mold, the horizontal mold size is 70*40*10cm, and the vertical mold size is 110*30*5cm; the mold temperature is 35-50°C, the overfilling rate is 15%-25%, and the demolding time is 150-300s.

[0039] Compared with the prior art, the present invention has the following positive effects:

[0040] 1) Organic acid is acidic. Under the same reaction activity, the catalyst content can be increased. In the later stage of the reaction, the foam begins to draw and transforms from liquid to solid. During this process, the acid disappears and the high-content catalyst begins to play a role, improving the foam ripening and demoulding properties. The foam becomes sticky after 240s of ripening. After adding organic acid, the foam becomes sticky after 180s, and the ripening performance is optimized by 60s. The average demoulding expansion of the original formula after 240s is 4.21%. After adding organic acid, the average demoulding expansion after 210s is 4.24%, and the demoulding performance is optimized by nearly 30s.

[0041] 2) After adding organic acid, the acidity disappears in the later stage, and the high catalyst content accelerates the foam gelation, affecting the movement of the foam in the final stage. Therefore, the foam has better surface bubbles, and the type A bubbles are reduced from 15 to 8.

[0042] 3) After adding organic acid, the catalyst content is high. Although the activity is lower, there are more active sites and the foam is finer. The pore size is reduced from 325nm to 172nm through scanning electron microscopy testing.

[0043] 4) Organic acids contain carboxyl groups, which can reduce the amount of water in the combined polyether and the production of polyurea. They can also improve the maturation and surface adhesion of the foam. The average adhesion of the foam is increased from 12kg.f to 17kg.f. DETAILED DESCRIPTION

[0044] The technical solution of the present invention is further illustrated by specific embodiments below, but the protection scope of the present invention is not limited thereto. Within the technical scope disclosed in the present invention, changes or replacements of the same or similar technical features should be covered within the protection scope of the present invention.

[0045] The sources of the main materials and reagents of the embodiments of the present invention are as follows:

[0046]

[0047] The manufacturers and models of the main instruments in the embodiments and comparative examples of the present invention are as follows:

[0048] Instrument Name model factory Thermal conductivity meter HC-074 EKO Equipment Compression strength machine 5Kn Proline Zwick / Roell High pressure foaming machine HK650 Hennecke Electron Microscope SIGMA 500 Zeiss Dynamometer SH-B Sandu Instruments Micrometer 468-174 Mitutoyo

[0049] Example 1

[0050] The raw material composition of the polyurethane rigid foam containing organic acid is a combination of polyether, polyisocyanate, organic acid, and foaming agent in a mass ratio of 100:150.1:1:12, specifically:

[0051] The combined polyether composition is as follows: polyether polyol A (hydroxyl value 465 mgKOH / g) 35.4 kg, polyether polyol B (hydroxyl value 498 mgKOH / g) 30 kg, polyether polyol C (hydroxyl value 362 mgKOH / g) 20 kg, polyether polyol D (hydroxyl value 251 mgKOH / g) 7 kg, surfactant B8481 2 kg, combined catalyst 3.5 kg, water 2.1 kg;

[0052] Among them, the combined catalyst: the foaming catalyst is 0.625 kg of pentamethyldiethylenetriamine, the gel catalyst is 2.125 kg of dimethylcyclohexylamine, and the trimerization catalyst is 0.75 kg of potassium acetate, and the corresponding mass ratio is pentamethyldiethylenetriamine: dimethylcyclohexylamine: potassium acetate = 1:3.4:1.2.

[0053] Polyisocyanate: Wanhua PM200 150.1kg;

[0054] Organic acid: anhydrous acetic acid 1kg;

[0055] Foaming agent: CP 12kg.

[0056] The steps for preparing polyurethane rigid foam are as follows:

[0057] S1: Weigh 35.4 kg of polyether polyol A, 30 kg of polyether polyol B, 20 kg of polyether polyol C, 7 kg of polyether polyol D, 2 kg of B8481, 3.5 kg of combined catalyst and 2.1 kg of water, mix well, and cool to 14° C. to obtain a mixture A;

[0058] S2: Add 2 kg of anhydrous acetic acid to mixture A, shake well, let stand for 4 hours, defoam, and cool to 14°C to obtain mixture B;

[0059] S3: Mixture B and 12 kg CP were mixed uniformly by rotation in a sealed pressure-bearing iron drum, and then allowed to stand for 8 h to obtain mixture C;

[0060] S4: Add mixture C and polyisocyanate to separate material tanks, mix and foam under high pressure to obtain polyurethane rigid foam. The high-pressure foaming material temperature is 18°C, the ratio of polyether mixture and polyisocyanate high-pressure foaming is 1:1.34, the gun head pressure is 125 bar, the flow rate is 500 g / s, and the mold temperature is 45°C. The following mold experiments are carried out respectively: the vertical mold size is 1100*300*50mm, and the demolding time is 240s, which is used to test the foam adhesion, thermal conductivity, compression strength, core density, pressure tank strength and dimensional stability; the horizontal mold size is 700*400*100mm, and the demolding time is 150s, 180s, 210s, and 240s, which is used to test the foam demolding performance and surface ripening performance; the L mold demolding time is 240s, which is used to test the bubbles on the foam surface.

[0061] Example 2

[0062] The raw material composition of the polyurethane rigid foam containing organic acid is a combination of polyether, polyisocyanate, organic acid, and foaming agent in a mass ratio of 100:154.6:2:12, specifically:

[0063] The combined polyether composition is as follows: polyether polyol A (hydroxyl value 465 mgKOH / g) 35.2 kg, polyether polyol B (hydroxyl value 498 mgKOH / g) 30 kg, polyether polyol C (hydroxyl value 362 mgKOH / g) 20 kg, polyether polyol D (hydroxyl value 251 mgKOH / g) 7 kg, surfactant B8481 2 kg, combined catalyst 4.0 kg, water 1.8 kg;

[0064] Among them, the combined catalyst: the foaming catalyst is 0.714 kg of pentamethyldiethylenetriamine, the gel catalyst is 2.429 kg of dimethylcyclohexylamine, and the trimerization catalyst is 0.857 kg of potassium acetate, and the corresponding mass ratio is pentamethyldiethylenetriamine: dimethylcyclohexylamine: potassium acetate = 1:3.4:1.2.

[0065] Polyisocyanate: Wanhua PM200 154.6kg;

[0066] Organic acid: anhydrous acetic acid 2kg;

[0067] Foaming agent: CP 12kg.

[0068] The method for preparing polyurethane rigid foam is the same as that in Example 1, and the ratio of the polyether mixture to the polyisocyanate high-pressure foaming is 1:1.38.

[0069] Example 3

[0070] The raw material composition of the polyurethane rigid foam containing organic acid is a combination of polyether, polyisocyanate, organic acid, and foaming agent in a mass ratio of 100:159.1:3:12, specifically:

[0071] The combined polyether composition is as follows: polyether polyol A (hydroxyl value 465 mgKOH / g) 35.1 kg, polyether polyol B (hydroxyl value 498 mgKOH / g) 30 kg, polyether polyol C (hydroxyl value 362 mgKOH / g) 20 kg, polyether polyol D (hydroxyl value 251 mgKOH / g) 7 kg, surfactant B8481 3 kg, combined catalyst 4.4 kg, water 1.5 kg;

[0072] Among them, the combined catalyst: the foaming catalyst is 0.786 kg of pentamethyldiethylenetriamine, the gel catalyst is 2.671 kg of dimethylcyclohexylamine, and the trimerization catalyst is 0.943 kg of potassium acetate, and the corresponding mass ratio is pentamethyldiethylenetriamine: dimethylcyclohexylamine: potassium acetate = 1:3.4:1.2.

[0073] Polyisocyanate: Wanhua PM200 159.1kg;

[0074] Organic acid: 3kg anhydrous acetic acid;

[0075] Foaming agent: CP 12kg.

[0076] The method for preparing polyurethane rigid foam is the same as that in Example 1, and the ratio of the polyether mixture to the polyisocyanate high-pressure foaming is 1:1.43.

[0077] Example 4

[0078] The polyurethane rigid foam containing organic acid has a raw material composition of a combination of polyether, polyisocyanate, organic acid, and foaming agent in a mass ratio of 100:154.1:1:17, specifically:

[0079] The composition of the combined polyether is as follows: 37.1 kg of polyether polyol A (hydroxyl value 465 mgKOH / g), 20 kg of polyether polyol B (hydroxyl value 498 mgKOH / g), 30 kg of polyether polyol C (hydroxyl value 362 mgKOH / g), 4 kg of polyether polyol D (hydroxyl value 251 mgKOH / g), 3 kg of surfactant Y12369, 4.4 kg of combined catalyst, and 1.5 kg of water;

[0080] Among them, the combined catalyst: the foaming catalyst is 0.88 kg of pentamethyldiethylenetriamine, the gelling catalyst is 2.55 kg of dimethylcyclohexylamine, and the trimerization catalyst is 0.97 kg of hexahydrotriazine, and the corresponding mass ratio is pentamethyldiethylenetriamine: dimethylcyclohexylamine: potassium acetate = 1:2.9:1.1.

[0081] Polyisocyanate: Wanhua PM200 154.1kg;

[0082] Organic acid: phenylacetic acid 1kg;

[0083] Foaming agent: CP 12kg, LBA 5kg.

[0084] The steps for preparing polyurethane rigid foam are as follows:

[0085] S1: Weigh 37 kg of polyether polyol A, 20 kg of polyether polyol B, 30 kg of polyether polyol C, 4 kg of polyether polyol D, 3 kg of Y16368, 4.5 kg of combined catalyst and 1.5 kg of water, mix well, and cool to 14° C. to obtain a mixture A;

[0086] S2: Add 1 kg of phenylacetic acid to mixture A, shake well, let stand for 4 hours, defoam, and cool to 14°C to obtain mixture B;

[0087] S3: Mixture B, 12 kg CP and 5 kg LBA were mixed uniformly by rotation in a sealed pressure iron drum and then allowed to stand for 8 hours to obtain mixture C;

[0088] S4: Add mixture C and polyisocyanate to separate material tanks, mix and foam under high pressure to obtain polyurethane rigid foam. The high-pressure foaming material temperature is 17°C, the ratio of polyether mixture and polyisocyanate high-pressure foaming is 1:1.32, the gun head pressure is 125 bar, the flow rate is 500 g / s, and the mold temperature is 45°C. The following mold experiments are carried out respectively: the vertical mold size is 1100*300*50mm, and the demolding time is 240s, which is used to test the foam adhesion, thermal conductivity, compression strength, core density, pressure tank strength and dimensional stability; the horizontal mold size is 700*400*100mm, and the demolding time is 150s, 180s, 210s, and 240s, which is used to test the foam demolding performance and surface ripening performance; the L mold demolding time is 240s, which is used to test the bubbles on the foam surface.

[0089] Example 5

[0090] The raw material composition of the polyurethane rigid foam containing organic acid is a combination of polyether, polyisocyanate, organic acid, and foaming agent in a mass ratio of 100:157.4:2:18, specifically:

[0091] The combined polyether composition is as follows: polyether polyol A (hydroxyl value 465 mgKOH / g) 36.8 kg, polyether polyol B (hydroxyl value 498 mgKOH / g) 20 kg, polyether polyol C (hydroxyl value 362 mgKOH / g) 30 kg, polyether polyol D (hydroxyl value 251 mgKOH / g) 4 kg, surfactant Y12369 3 kg, combined catalyst 4.9 kg, water 1.3 kg;

[0092] Among them, the combined catalyst: the foaming catalyst is 0.98 kg of pentamethyldiethylenetriamine, the gelling catalyst is 2.84 kg of dimethylcyclohexylamine, and the trimerization catalyst is 1.08 kg of hexahydrotriazine, and the corresponding mass ratio is pentamethyldiethylenetriamine: dimethylcyclohexylamine: potassium acetate = 1:2.9:1.1.

[0093] Polyisocyanate: Wanhua PM200 157.4kg;

[0094] Organic acid: phenylacetic acid 2kg;

[0095] Foaming agent: CP 10kg, LBA 8kg.

[0096] The method for preparing polyurethane rigid foam is the same as that in Example 1, and the ratio of the polyether mixture to the polyisocyanate high-pressure foaming is 1:1.33.

[0097] Example 6

[0098] The raw material composition of the polyurethane rigid foam containing organic acid is a combination of polyether, polyisocyanate, organic acid, and foaming agent in a mass ratio of 100:159.4:3:18, specifically:

[0099] The combined polyether composition is as follows: polyether polyol A (hydroxyl value 465 mgKOH / g) 36.2 kg, polyether polyol B (hydroxyl value 498 mgKOH / g) 20 kg, polyether polyol C (hydroxyl value 362 mgKOH / g) 30 kg, polyether polyol D (hydroxyl value 251 mgKOH / g) 4 kg, surfactant Y12369 3.5 kg, combined catalyst 5.3 kg, water 1.0 kg;

[0100] Among them, the combined catalyst: the foaming catalyst is 1.06 kg of pentamethyldiethylenetriamine, the gelling catalyst is 3.07 kg of dimethylcyclohexylamine, and the trimerization catalyst is 1.17 kg of hexahydrotriazine, and the corresponding mass ratio is pentamethyldiethylenetriamine: dimethylcyclohexylamine: potassium acetate = 1:2.9:1.1.

[0101] Polyisocyanate: Wanhua PM200 159.4kg;

[0102] Organic acid: phenylacetic acid 3kg;

[0103] Foaming agent: CP 10kg, LBA 8kg.

[0104] The method for preparing polyurethane rigid foam is the same as that in Example 1, and the ratio of the polyether mixture to the polyisocyanate high-pressure foaming is 1:1.35.

[0105] Table 1 Composition (weight, kg) and performance parameters of polyurethane rigid foam raw materials in Examples 1-6

[0106]

[0107]

[0108] Note: Foam density, compression strength, thermal conductivity and dimensional stability are all measured according to national standards:

[0109] Foam core density test according to standard: GB / T 6343-2009;

[0110] Foam thermal conductivity test is in accordance with the standard: GB / T 10295-2008;

[0111] Foam compression strength test according to standard: GB / T 8813-2008;

[0112] The foam dimensional stability test is in accordance with the standard: GB / T 8811-2008.

[0113] Surface bubble standard: diameter ≥ 2cm.

[0114] Comparative Example 1

[0115] In Example 1, 1 kg of anhydrous acetic acid was removed because the reaction was faster under non-acidic conditions, and a lower combined catalyst content was required, the weight was 2.3 kg, the density was higher, the water content was increased to 2.5 kg, and the polyether polyol A was increased to 36.2 g. The other components were the same as in Example 1.

[0116] The method for preparing polyurethane rigid foam is the same as that in Example 1, and the ratio of the polyether mixture to the polyisocyanate high-pressure foaming is 1:1.34.

[0117] Comparative Example 2

[0118] In Example 4, 1 kg of phenylacetic acid was removed because the reaction was faster under non-acidic conditions, and a lower combined catalyst content was required, the weight was 3.2 kg, the density was higher, the water content was increased to 1.9 kg, and the polyether polyol A was increased to 37.9 g. The other components were the same as in Example 4.

[0119] The method for preparing polyurethane rigid foam is the same as that in Example 4, and the ratio of the polyether mixture to the polyisocyanate high-pressure foaming is 1:1.32.

[0120] Table 2 Performance parameters of polyurethane rigid foam prepared in Comparative Examples 1-2

[0121]

[0122]

[0123] From the comparison of the above embodiments and the comparative examples, it can be found that the polyurethane rigid foam prepared by the scheme of the present invention has higher compression strength, smaller pressure tank deformation rate, lower thermal conductivity, and optimized aging by nearly 60s, and the demolding performance is also optimized by 30s, and the thermal conductivity is lower, under the same core density conditions, thereby reflecting more excellent comprehensiveness.

[0124] Those skilled in the art will appreciate that, based on the teachings of this specification, some modifications or adjustments may be made to the present invention, and these modifications or adjustments should also be within the scope defined by the claims of the present invention.

Claims

1. A polyurethane rigid foam, characterized in that: The raw materials of the polyurethane rigid foam contain organic acid, and the raw materials of the polyurethane rigid foam include the following components: Wherein, the general structural formula of the organic acid is as follows: Wherein, n is an integer not less than 0, and R is -CH3 or -Ph; The composite polyether comprises: 89.5-94 parts of mixed polyether polyol, 3.5-5.5 parts of composite catalyst, 1.5-3.5 parts of surfactant, and 1.0-2.5 parts of water; The combined catalyst in the combined polyether is: one or more of opalescent pentamethyldiethylenetriamine, tetramethylhexanediamine and bis-dimethylaminoethyl ether; one or more of gel-type catalysts dimethylbenzylamine, dimethylcyclohexylamine, triethylenediamine and methylimidazole; one or more of trimerization catalysts potassium acetate, hexahydrotriazine and quaternary ammonium salt; The relationship between the content of the combined catalyst and the content of the organic acid is as follows: Where m0 is the mass of the combined catalyst without organic acid, m e is the mass of the combined catalyst, m c The mass of organic acid.

2. The polyurethane rigid foam according to claim 1, characterized in that In the general structural formula of the organic acid, n is an integer of 0-3.

3. The polyurethane rigid foam according to claim 1, characterized in that The mixed polyether polyol comprises one or more of the following polyols: Polyether polyol A: prepared by addition reaction of sorbitol as initiator with propylene oxide, with a viscosity of 25,000-35,000 mPa.s, a hydroxyl value of 350-550 mgKOH / g, and a functionality of 5.5-6.0; Polyether polyol B: sucrose and glycerol are used as initiators, and undergo addition reaction with propylene oxide, with a viscosity of 8,000-15,000 mPa.s, a hydroxyl value of 450-600 mgKOH / g, and a functionality of 4.6-5.8; Polyether polyol C: o-toluenediamine is used as the initiator, and first reacts with ethylene oxide for addition reaction. After the reaction, propylene oxide is added for addition reaction. The viscosity is 35,000-55,000 mPa.s, the hydroxyl value is 340-460 mgKOH / g, and the functionality is 3.4-3.9; Polyether polyol D: Diethylene glycol is used as an initiator, and undergoes an addition reaction with propylene oxide. The viscosity is 50-100 mPa.s, the hydroxyl value is 200-300 mgKOH / g, and the functionality is 2.

0.

4. The polyurethane rigid foam according to claim 1, characterized in that The polyisocyanate is polymeric MDI.

5. The polyurethane rigid foam according to claim 4, characterized in that The polyisocyanate is polymeric MDI having an NCO content of 30 wt% to 32 wt%; The mass content of the polyisocyanate has the following formula: Among them, m b is the mass of isocyanate, m a is the mass of the combined polyether, m d is the mass of foaming agent, m c is the mass of organic acid, M c is the molecular weight of organic acid.

6. The polyurethane rigid foam according to claim 5, characterized in that The polyisocyanate is one or more of Wanhua PM-200, Wanhua PM-2010 and Wanhua PM-400.

7. The polyurethane rigid foam according to claim 1, characterized in that: The -COOH group contained in the organic acid can react with isocyanate to generate CO2, which is retained in the pores.

8. The polyurethane rigid foam according to claim 1, characterized in that The foaming agent is a single foaming agent or a mixed foaming agent, which at least contains a CP foaming agent.

9. A method for preparing a polyurethane rigid foam, wherein the rigid foam is the polyurethane rigid foam according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: S1: uniformly mixing a mixed polyether polyol, a surfactant, a composite catalyst and water, and cooling the mixture to obtain a combined polyether mixture A; S2: adding organic acid to mixture A, shaking, standing, and cooling to obtain mixture B; S3: After the mixture B and the foaming agent are evenly mixed, a mixture C is obtained; S4: Add the mixture C and the polyisocyanate into independent foaming machine material tanks respectively, mix and foam them under high pressure, and then inject them into a mold to obtain polyurethane rigid foam.

10. The preparation method according to claim 9, characterized in that: In the steps S1 and S2, the material is cooled to below 15°C; in the step S4, the conditions for high pressure foaming are material temperature 15-20°C and pressure 100-150 barG.

11. The preparation method according to claim 10, characterized in that: The conditions for high pressure foaming in step S4 are material temperature 17-18° C. and pressure 125-130 barG.

Citation Information

Patent Citations

  • Rigid polyurethane foams

    CN1235617A